(untitled) (Window of Public Health Journal, 2025)
According to the World Health Organization, obesity is a condition of excessive body weight or obesity that exceeds the body mass index. Obesity often occurs because the calories consumed are more than those burned through physical activities such as sports and others. Therefore, fat in the body accumulates which causes obesity. Obesity is the most common condition that can be experienced by children, adolescents or adults. A person who is at high risk of obesity is if he does not maintain a diet and does enough exercise. The purpose of this study was to determine the effect of consumption of ultra-processed foods or drinks on the incidence of obesity in female adolescents at SMK-SMAK Makassar. The type of research is a quantitative design with a cross-sectional study design. The population in this study were all female students in grade XI as many as 130 students with a sampling technique using the total sampling method. With a sample size of 130 students. The type of data analysis used was univariate and bivariate analysis with a logistic regression test using the SPSS application with a confidence level of 95% (0.05). The conclusion is that our thorough research process, including univariate and bivariate analysis with a logistic regression test using the SPSS application, has revealed a significant influence between the consumption of ultra-processed foods on the incidence of obesity in female adolescents in grade XI at SMK-SMAK Makassar, and equally importantly, there is no influence between the consumption of ultra-processed drinks on the incidence of obesity in female adolescents in grade XI at SMK-SMAK Makassar.